Correction to: Formative research for the design of a scalable water, sanitation, and hygiene mobile health program: CHoBI7 mobile health program - Christine Marie George; Fatema Zohura; Alana Teman; Elizabeth Thomas; Tasdik Hasan; Sohel Rana; Tahmina Parvin; David A. Sack; Sazzadul Islam Bhuyian; Alain Labrique; Jahed Masud; Peter Winch; et al. (BMC, 2019)
It was highlighted that the original article [1] contained an error in the title. Additionally, Table 2 contained a typesetting mistake. This Correction article shows the incorrect and correct article title and Table 2. The original article has been updated.